Institute of Skill Development and Training : keeping an 'eye' on strategic cost efficiency - Desai, Naman (London : Indian Institute of Management, Ahmedabad, 2020)
The Institute of Skill Development and Training (ISDT) was established in 2009 by a Nashik based entrepreneur, Yogesh Kothari (Nashik is a city in the western Indian state of Maharashtra). ISDT started as a two-person operation in 2009; and by 2019, it had grown to a 32-employee operation with presence in 18 states in India. ISDT also employed approximately 40 associates to conduct training programmes across India. Looking back at the 10 years the institute had completed, Kothari seemed satisfied with the way things had progressed; however, he felt it was time he evaluated the profitability and long-term sustainability of the programmes the institute offered. The case provides an opportunity to understand the business model of the Institute of Skill Development and Training (ISDT), and its applicability in addressing vision related issues in India. The case also offers opportunities to participants to understand the application of an Activity Based Costing Model in a service context.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cost effectiveness -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies